Cognitive performance in a subclinical obsessive-compulsive sample: Emotional processing and quality of life. Issue 2 (3rd April 2017) - Johansen, Thomas; Dittrich, Winand H.
Abstract: There is a stronger focus on understanding emotional processing in obsessive-compulsive disorder (OCD). This follows the assumption that the orbitofrontal cortex may be impaired. The ability to recognize and name odours probe emotional processing and thus orbitofrontal cortex functioning. The aim of this exploratory study was to investigate whether olfactory naming performance in individuals reporting subclinical obsessive-compulsive (OC) tendencies is impaired. This would allow a better understanding of differences and similarities in emotional processing between OCD patients and individuals reporting OC tendencies. The assessment of OC tendencies was measured with two standardized questionnaires (Yale-Brown Obsessive Compulsive Disorder Scale and Cognitive Assessment Instrument of Obsessions and Compulsions). The performance on a smell naming test in a subclinical group was compared to a group of individuals not reporting OC tendencies, and constituted the nonclinical control group. The subclinical group performed to the same standard as the nonclinical control group in naming both unpleasant and pleasant smells. It cannot be assumed that individuals showing OC tendencies are impaired in emotional processing as found in diagnosed OCD patients. Nevertheless, it is argued that the interaction between cognition and emotion, for example, intact attentional processing of emotional information is vital to reduce the intensity, frequency and duration of OC tendencies, thus underpinning experiences that promote better quality of social and working life.